Typification and a new synonym of Liparis atropurpurea (Orchidaceae) - Arigela, Ravi Kiran; Singh, Rajeev Kumar; Jalal, Jeewan Singh (Phytotaxa, 2019)
The genus Liparis Richard (1817: 21) composed of about 400 species (Mabberley 2017), widely distributed in tropical, subtropical and temperate areas of the World with maximal diversity in tropical Asia (Chen et al. 2009). In India it is represented by 51 species (Misra 2007).